Forgetting Patterns Differentiate Between Two Forms of Memory Representation. (June 2016) - Sadeh, Talya; Ozubko, Jason D.; Winocur, Gordon; Moscovitch, Morris
For decades, there has been controversy about whether forgetting is caused by decay over time or by interference from irrelevant information. We suggest that forgetting occurs because of decay or interference, depending on the memory representation. Recollection-based memories, supported by the hippocampus, are represented in orthogonal patterns and are therefore relatively resistant to interference from one another. Decay should be a major source of their forgetting. By contrast, familiarity-based memories, supported by extrahippocampal structures, are not represented in orthogonal patterns and are therefore sensitive to interference. In a study in which we manipulated the postencoding task-interference level and the length of the delay between study and testing, we provide direct evidence in support of our representation theory of forgetting. Recollection and familiarity were measured using the remember/know procedure. We show that the causes of forgetting depend on the nature of the underlying memory representation, which places the century-old puzzle of forgetting in a coherent framework.